IMPLEMENTASI KEBIJAKAN BEASISWA BIDIKMISI TAHUN 2010-2014 (STUDI PENELITIAN DI UNIVERSITAS DIPONEGORO DAN UNIVERSITAS NEGERI SEMARANG) - RAHMAWATI .; Sulistyowati .; Nunik Retno Herawati (Journal of Politic and Government Studies, 2016)
ABSTRACTPolicy implementation of Bidikmisi scholarship 2010-2014 study research at the Diponegoro University and Semarang State University has the objective to investigate the implementation of the policy at the Diponegoro University and Semarang State University. The implementation is to know Bidikmisi scholarship policy implementation based on the theory of policy implementation by Donald S. Van Meter and Carl E. Van Horn with six indicators, which is standards and policy goals, resources, communications, disposition implementer, characteristics enforcement agencies, and social environment, economic and political.The method of answering the problem in this research is a qualitative deskripstif main data types are the words and actions. Sources of data obtained derived from primary data and secondary data. Search informants with purposive sampling system (making intentional) and accidental sampling (sampling by accident when he met at the study site). Collection techniques using interviews, observation, and documents.Bidikmisi scholarship policy is a policy of the central government through the Ministry of Research, Technology, and Higher Education (formerly the Ministry of Education and Culture) which refers to public and private universities to do the job. This policy has a major goal is to break the chain of poverty by providing opportunities high achieving students who have financial limitations for education in college. This policy has the same guidelines with all rules and regulations. However, in practice, Diponegoro University and Semarang State University had differences in management.Results from this study is expected to provide benefits for the government to regulate clearer to the college so that the principle such as right on target, right number, and timely of these policies can be achieved.Keywords: Implementation of Government Policy, Bidikmisi Scholarship